Educate educators: Interactive infographics hands-on-training to foster teacher's visual literacy - Eline Rozaliya Winarto; Dila Charisma; Sumliyah Sumliyah; Intan Jahni; Irka Fitri Adha (Community Empowerment, 2024)
The lack of ability among SMPN 1 Jamblang teachers to utilize infographics resulted in low student engagement and a lack of variation in teaching methods. This community service aimed to improve teachers' ability to use infographics as interactive and effective learning tools to enhance the quality of education and student engagement. Activities included initial socialization and a focus group discussion (FGD), followed by a workshop on creating infographics using Canva and Prezi, and training on effective design principles. Monitoring and evaluation were conducted via WhatsApp groups and collaborative assignments uploaded to Google Drive to facilitate feedback and peer learning. Results showed increased teacher proficiency in creating informative and engaging infographics, boosted self-confidence (particularly among teachers previously struggling with technology), and greater enthusiasm for and integration of technology into teaching.